The Creation of New Public Spaces in Central America at the Beginning of the 20th Century: The Influence of Theosophical Networks on Central American Public Opinion - Casaús Arzú, Marta Elena (2002)
The theme of the formation of associations, clubs, Masonic lodges, etc., through which close ties, interpersonal and intellectual relationships are established that will later generate public opinion and consensus among different intellectual and political elites, without necessarily having to share common ideological ties, has produced a rich bibliography about these associative practices in which secularized republics germinated, built on new citizen values and forms of collective representation. However, in Central America (especially Guatemala) this issue has not been dealt with much from the perspective of public opinion and social networks, crossing both variables could be analyzed as a vertebrating space of civil society, a sphere that generates public opinion that is shaping a new community of citizens.